Computer-Human Interaction 8th Asia-Pacific Conference, APCHI 2008 Seoul, Korea, July 6-9, 2008 Proceedings - Lee, Seongil; Choo, Hyunseung; Ha, Sungdo; Shin, In Chul.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2008)
This book constitutes the refereed proceedings of the 8th Asia Pacific Conference on Computer Human Interaction, APCHI 2008, held in Seoul, Korea, in July 2008. The 45 revised full papers presented together with 6 invited papers were carefully reviewed and selected from 151 submissions. The topics addressed span the entire spectrum of HCI, including ubiquitous computing, groupware, intelligent system design, human-robot interaction, virtual / augmented environment, vision-based system, mobile interaction design, novel interaction technique, usability, Web accessibility, and elderly.
Ubiquitous Computing -- Experience of Enhancing the Space Sensing of Networked Robots Using Atlas Service-Oriented Architecture -- A Formal Model of Coordination for Supporting Community Computing in a Ubiquitous Environment -- A User-Centered Approach for Ubiquitous Service Evaluation: An Evaluation Metrics Focused on Human-System Interaction Capability -- On Generating Backbone Trees through Robust Multi-hop Clusters in Wireless Sensor Networks -- Denial of Sleeping: Performance Analysis and Counteracting Strategy -- Groupware -- Eye, Robot: A Network Control System for Ophthalmologic Examination -- A Study of a Loosely-Coupled Groupware System for Supporting Collaboration and Coordination -- RIKI: A Wiki-Based Knowledge Sharing System for Collaborative Research Projects -- Intelligent System Design -- Unconsciously Harmonized Online Communication Based on Uninterruptibility Estimation of Interaction Partners -- A Novel Web Page Analysis Method for Efficient Reasoning of User Preference -- Mood and Recommendations: On Non-cognitive Mood Inducers for High Quality Recommendation -- Intelligent Information System Based on a Speech Web Using Fuzzy Association Rule Mining -- Restaurant Recommendation for Group of People in Mobile Environments Using Probabilistic Multi-criteria Decision Making -- Human-Robot Interaction -- Augmented Reality Based Vision System for Network Based Mobile Robot -- Embedded Robot Operating Systems for Human-Robot Interaction -- A User Interface Transmission System for Public Robots -- Development of a WS-ECA Rule Management System for a Healthcare Robot -- Virtual/Augmented Environment -- Making Reading Experience Rich with Augmented Book Cover and Bookmark -- SPATIAL POEM: A New Type of Experimental Visual Interaction in 3D Virtual Environment -- Human Genome Data Visualization Using a Wall Type Display -- An Experience with Augmenting a Mirror as a Personal Ambient Display -- Vision-Based System -- Universal Video Adaptation Model for Contents Delivery in Ubiquitous Computing -- Selective Visual Attention System Based on Spatiotemporal Features -- A Technique for Displaying Presence Information on a Live Camera Image Using 3-D Mask Objects -- Background Subtraction Based on Local Orientation Histogram -- Relationship between Viewing Distance and Visual Fatigue in Relation to Feeling of Involvement -- Mobile Interaction Design -- Tactile Icon Design Using a Vibration Actuator in Mobile Devices -- Design of 3D Mobile Phones and Application for Visual Communication -- A Comparative Evaluation of User Preferences for Mobile Chat Usable Interface -- The Impact of Multimedia Extensions for Multimedia Applications on Mobile Computing Systems -- Novel Interaction Technique -- The Use of Photo Retrieval for EEG-Based Personal Identification -- Music Wall: A Tangible User Interface Using Tapping as an Interactive Technique -- Double-Crossing: A New Interaction Technique for Hand Gesture Interfaces -- Acquisition of Off-Screen Object by Predictive Jumping -- Hands-Free Input Interface Using Mimetic Muscle Movements for Wearable Computer -- Muscle Loadings While Using Finger as Input Device -- Design and Analysis of Conceptual Sketches Based on Context Awareness -- Accuracy of Velocity Perception Generated by Tactile Apparent Motion -- Usability -- A New Framework on Measuring Customer Perceived Value in Service Interface Design -- Novice Word Processor User Performance with Pictorial and Text Icons -- Exploring Factors That Make Online Interactive Games Successful: A Heuristic Approach -- Users$1 (BPerception and Usability Study of a Parser for Headings -- Development of Interactive Map-Based Tour Information System for Busan -- Web Accessibility -- Development of Image and Color Evaluation Algorithm for the Web Accessibility Evaluation Tools -- Longitudinal Study on Web Accessibility Compliance of Government Websites in Korea -- Korean Web Site Usability for Disabled People -- A Proxy-Based System for Translation of Internet Content into Specific Form -- The Elderly -- Extracting the Components of Elderly People$1 (Bs Capacity in Electrical Appliances and Grasping Relationship with the Components -- The Choice of Communication Media and the Use of Mobile Phone among Senior Users and Young Users -- Prototyping and Evaluation for Smart Home Controller Based on Chinese Families Behavior Analysis -- Mapping User Accessibility Needs Systematically to Universal Design Principles.s
Keywords: Computer science; Database management; Information storage and retrieval; User interfaces (Computer systems).; Artificial intelligence; Computer engineering; Computer Science; User Interfaces and Human Computer Interaction; Database Management; Computer Engineering; Information Storage and Retrieval; Information Systems Applications (incl. Internet).; Artificial Intelligence (incl. Robotics).; Electronic books